Expression of 14-3-3 Zeta Protein in Dexamethasone-Treated Mice and Human TM-1 Cells. (3rd August 2017) - Liu, Qian; Ye, Yiming; Lin, Xianchai; Yang, Yangfan; Wu, Kaili; Yu, Minbin
ABSTRACT: Purpose : 14-3-3 zeta protein plays a potential protective role in neurodegenerative disease. Given that glaucoma and neurodegenerative diseases share a similar pathogenesis, it is possible that 14-3-3 zeta may have a similar protective effect in the glaucomatous process. In the present study, we measured the expression of 14-3-3 zeta in vivo (mouse eyes) and in vitro in a transformed human trabecular meshwork (HTM) cell line, TM-1, and assessed the possible roles of this protein in dexamethasone (DEX)-treated eyes and HTM cells. Methods : Mouse eyes were randomly treated with 0.1% dexamethasone (DEX) eye drops or phosphate-buffered solution (PBS) for 28 days. The expression and distribution of 14-3-3 zeta protein in mouse eyes were examined using immunofluorescence. TM-1 cells were treated with DEX (10 −6 or 10 −7 M) or PBS for 1, 4, or 7 days, and the mRNA and protein expression of 14-3-3 zeta were detected by real-time RT-PCR and Western blotting. Results : 14-3-3 zeta protein was highly expressed in the mouse cornea, trabecular meshwork (TM), and ciliary body. Intraocular pressure (IOP) was significantly elevated, whereas the 14-3-3 zeta expression was significantly decreased in mouse TM after 0.1% DEX treatment for 28 days. In vitro, treatment with 10 −7 M DEX mildly increased 14-3-3 zeta mRNA and protein expression ( p > 0.05), whereas 10 −6 M DEX significantly decreased expression of 14-3-3 zeta mRNA and protein ( p < 0.05) compared to the control (Ctrl) group at the seventh day. Conclusions : DEX can increase IOP in mouse eyes and concurrently downregulate 14-3-3 zeta protein expression in mouse TM. The effects of DEX on 14-3-3 zeta expression in vitro were both dose- and time-related. Our results suggest that alterations in 14-3-3 zeta protein may be implicated in DEX-induced pathological elevated IOP.